КЛЮЧОВІ ПОКАЗНИКИ ЕФЕКТИВНОСТІ ДІЯЛЬНОСТІ УНІВЕРСИТЕТУ В РЕАЛІЗАЦІЇ СТРАТЕГІЇ ФОРМУВАННЯ ФІНАНСОВОГО ПОТЕНЦІАЛУ (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. In the period of transformational changes, integration of the higher education system into the worldeducation space and its permanent reform, determining the effective activities of universities, their place in therankings and on the market of educational and scientific services occupies a leading position in management.The purpose of the article. The purpose of the article is to form KPIs to assess the results of educational andscientific activities of Ukrainian higher education institutions (HEIs), improvement of their financial capacity, as wellas increase in the effectiveness of financial and economic activities.Results. Foreign experience of the implementation of HEIs development strategies on the basis of a cleardefinition of KPIs, in particular, financial ones, is studied. Examining the goals and objectives of Ukrainianuniversities, their development strategies, and comparing them with world prominent HEIs, we see a clear similarity inthe development of fundraising activities and increase in cooperation with the market environment, stakeholders,alumni, donors, philanthropists and others. However, transparency and publicity, development of methods andmechanisms of financial management, definition of clear KPIs remain relevant issues for Ukrainian HEIs nowadays.Conclusions. We consider that achieving a level of competitive HEI is not possible without a developmentstrategy with defined strategic, tactical and current goals, clear tasks and monitoring of their implementation. It isproposed to launch the system of KPIs for HEIs and its application in the process of financial management which willfoster achieving the results and transparency of HEI activity. In our opinion, defining common KPIs and theirobligatory implementation will allow a chief funds administrator to monitor and timely adjust, if necessary, his/heractions, conduct a comparative assessment of the entire higher education system, and university management provideanalysis, control and increase in performance and financial capacity, while stakeholders have access to reliableinformation. The fulfillment of this set of tasks and goals, the achievement of KPIs, in particular, financial ones willpermit to form a strong financial potential of HEI, its development strategy and ensure financial stability and,consequently, competitiveness on the global market of educational and scientific services.
Keywords: higher education institutions, u